THE TEACHERS' CLINIC. - Kaulback, Frank S.; Moss, Morton F.; Van Voorhis, Robert H.; Smyth, J. E. (The Accounting Review, 1954)
Abstract This article presents information the teaching methods of accounting. Beyond the first few weeks of the elementary course, too little emphasis is placed on the fundamental accounting equation. As a result the student threads his way through the first year of accounting at best understanding certain relationships in vacuo but probably in most cases accepting them on faith. He then proceeds to memorize these relationships and hopes that the examination situation will be sufficiently similar to the one he learned by rote so that he can cope with it. Perhaps the ideal solution to this difficulty is one which places greater stress on the equation in the first course in accounting, but this probably would require a fundamental revision of course structure with the concomitant sacrifice of other worth-while materials. One result that follows from this lack of stress on the equation is the necessity to spend the first part of the second course in accounting on a general review of the basic accounting process.